2008
DOI: 10.2967/jnumed.107.044727
|View full text |Cite
|
Sign up to set email alerts
|

Initial Characterization of an 18F-Labeled Myocardial Perfusion Tracer

Abstract: PET allows for quantitative, regional myocardial perfusion imaging. The short half-lives of the perfusion tracers currently in use limit their clinical applicability. Here, the biodistribution and imaging quality of a new 18 F-labeled myocardial perfusion agent ( 18 F-BMS-747158-02) in an animal model are described. Methods: The biodistribution of 18 F-BMS-747158-02 was determined at 10 and 60 min after injection. The first-pass extraction fraction of the tracer was measured in isolated rat hearts perfused wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
177
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(187 citation statements)
references
References 25 publications
9
177
0
1
Order By: Relevance
“…However, this technique measures only the first part of glucose metabolism in the phosphorylation of glucose to glucose-6-phosphate by hexokinase (EC 2.7.1.1). Therefore, 18 F-FDG is taken up into not only normal tissues but also inflammatory regions observed in the subacute phase after transient focal ischemia in rodent models (11,12). Because recent reports indicated that several neurodegenerative disorders-schizophrenia, major depression, dementia (13,14), and autism (15)-induced neuroinflammation, 18 F-FDG may lead to underestimation of the neurodegenerative damage in these diseases.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, this technique measures only the first part of glucose metabolism in the phosphorylation of glucose to glucose-6-phosphate by hexokinase (EC 2.7.1.1). Therefore, 18 F-FDG is taken up into not only normal tissues but also inflammatory regions observed in the subacute phase after transient focal ischemia in rodent models (11,12). Because recent reports indicated that several neurodegenerative disorders-schizophrenia, major depression, dementia (13,14), and autism (15)-induced neuroinflammation, 18 F-FDG may lead to underestimation of the neurodegenerative damage in these diseases.…”
mentioning
confidence: 99%
“…In contrast, activated inflammatory cells (macrophages and microglia) (4-7) and cancer cells (3,8,9) produce lactate from glucose via lactate dehydrogenase subunit A (EC 1.1.1.27), which is known as the Warburg effect or aerobic glycolysis, showing less than 5% glucose utilization in oxidative phosphorylation and a low contribution of the electron transport system for adenosine triphosphate (ATP) production. 18 F-FDG PET is a well-established technique for the quantitative measurement of the regional metabolic rate of glucose in the brain (10). However, this technique measures only the first part of glucose metabolism in the phosphorylation of glucose to glucose-6-phosphate by hexokinase (EC 2.7.1.1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has been known for long with 15 O-water which does not produce qualitative perfusion images at all but only quantitative results. The same phenomenon is likely to happen automatically with the new tracers with high extraction fraction 12,13 and also with other tracers after quantification. This means that the traditional criteria for ischemic regions in the images need to be redefined when quantification is applied.…”
Section: Interpretation Of Absolute Myocardial Perfusion Resultsmentioning
confidence: 97%
“…16 There are, however, some obvious differences between these two tracers. 13 N-ammonia is extracted from blood with an extraction fraction lower than 100% and the extraction is inversely related to the perfusion (Figure 1). When 15 O-water is used, perfusion is estimated from the tracer's washout from the myocardium, whereas with 13 N-ammonia, perfusion is calculated from the tracer's uptake by myocardium.…”
Section: The Techniques Of Myocardial Perfusion Quantificationmentioning
confidence: 99%